“Strangers and Aliens on Earth” (Hebrews 11:13b): A Socio-Exegetical Inquiry into Christians’ Rite of Passage - Ogunbiyi, David Oluwabukunmi; Adedibu, Babatunde Aderemi (Darul Yasin Al Sys, 2025)
This study examines the theological and sociological significance of Christian rites of passage through the interpretive lens of Hebrews 11:13b, which portrays believers as “strangers and aliens on the earth.” Adopting a socio-exegetical approach, it explores how this pilgrim identity informs Christian perceptions and practices of baptism, marriage, and funeral rites within selected Nigerian denominations, including Anglican, Methodist, Pentecostal, and Indigenous Churches. Guided by Van Gennep’s rites of passage framework and Victor Turner’s concepts of liminality and communitas, the research integrates biblical exegesis with liturgical theology to assess the spiritual meaning of these rituals. Data gathered from 900 respondents indicate strong affirmation of pilgrim theology and broad consensus that Christian rites function as spiritual milestones symbolizing detachment from worldly values and anticipation of eternal life. Baptism and funeral rites are particularly valued for their eschatological significance, while perspectives on marriage as a symbolic pointer to heavenly realities are more diverse. The study also uncovers tensions between Christian doctrine and African traditional death practices, highlighting the need for contextual theological dialogue. It concludes that the Church bears a vital pastoral responsibility in preparing believers for the ultimate transition death by reaffirming the biblical vision of heavenly citizenship. The findings recommend enriched liturgical expression, deeper theological formation, and intentional youth engagement to sustain a spiritually grounded yet culturally sensitive practice of Christian rites. Ultimately, these rites are shown to function not only as markers of life transitions but as embodiments of the Christian journey toward God’s eternal promise.